2024
DOI: 10.7554/elife.88420
|View full text |Cite
|
Sign up to set email alerts
|

Comparative brain-wide mapping of ketamine- and isoflurane-activated nuclei and functional networks in the mouse brain

Abstract: Ketamine (KET) and isoflurane (ISO) are two widely used general anesthetics, yet their distinct and shared neurophysiological mechanisms remain elusive. In this study, we conducted a comparative analysis of KET and ISO effects on c-Fos expression across the brain, utilizing principal component analysis (PCA) and c-Fos-based functional network analysis to evaluate the responses of individual brain regions to each anesthetic. Our findings demonstrate that KET significantly activates cortical and subcortical arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Therefore, the downstream (or outputs) of the neuronal circuits associated with these behavioral and psychological traits would be strongly disturbed during anesthesia. Indeed, a large number of the research reported the differences in activity of neurons, neural population, and functional connectivity of brain areas between anesthetized and awake conditions (Nallasamy and Tsao, 2011;Sellers et al, 2015;Hu et al, 2024). However, the upstream and peripheral of each circuit, such as sensory representation in the primary or secondary sensory areas, may be less disturbed by anesthesia.…”
Section: Sensory Response In Anesthetized and Awake Conditionmentioning
confidence: 99%
“…Therefore, the downstream (or outputs) of the neuronal circuits associated with these behavioral and psychological traits would be strongly disturbed during anesthesia. Indeed, a large number of the research reported the differences in activity of neurons, neural population, and functional connectivity of brain areas between anesthetized and awake conditions (Nallasamy and Tsao, 2011;Sellers et al, 2015;Hu et al, 2024). However, the upstream and peripheral of each circuit, such as sensory representation in the primary or secondary sensory areas, may be less disturbed by anesthesia.…”
Section: Sensory Response In Anesthetized and Awake Conditionmentioning
confidence: 99%